Multinary platelet-shaped nanocomposites, methods of making, and applications in oer, uor, and overall water splitting

CN117646245BActive Publication Date: 2026-10-30ANHUI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311555848.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2026-10-30
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

但是其没有公开OER、UOR和尿素全解水的应用

Benefits of technology

[0035]与现有技术相比,本发明具有以下优点:制备方法简单,反应条件温和,所需试剂及设备简单;使用非贵金属和稀土元素做原料极大降低成本;OER过程中,在大电流电流密度下有着极佳的催化性能;在尿素氧化(UOR)和尿素全解水催化中效果表现良好;催化剂稳定性极佳。所合成制备的电化学催化剂,可用于析氧反应(OER)、尿素氧化反应(UOR)、和全尿素水解反应(OUS)的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117646245B_ABST
    Figure CN117646245B_ABST
Patent Text Reader

Abstract

The application provides a multi-element sheet-shaped nanocomposite, a preparation method and application in OER, UOR and total urea water splitting, and the multi-element sheet-shaped nanocomposite is prepared by the following steps: placing foam nickel in a mixed solution of a cobalt source, a cerium source, an organic ligand and a solvent, and performing hydrothermal reaction to obtain the foam nickel covered with a CeO2 / Co(OH)2 precursor; and then placing the foam nickel in a mixed solution of an iron source, a sulfur source and a solvent, and performing hydrothermal reaction to obtain the multi-element sheet-shaped nanocomposite. Compared with the prior art, the application has the following advantages: the preparation method is simple, the reaction condition is mild, and the cost is low; in the OER process, the multi-element sheet-shaped nanocomposite has excellent catalytic performance under a large current density; the multi-element sheet-shaped nanocomposite has good performance in urea oxidation (UOR) and total urea water splitting catalysis; and the catalyst has excellent stability. The electrochemical catalyst prepared by the application can be used in oxygen evolution reaction (OER), urea oxidation reaction (UOR) and total urea water splitting reaction (OUS).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of inorganic nanomaterials and electrochemical catalyst preparation research, and involves multi-component sheet-like nanocomposites and their preparation methods, as well as their applications in OER, UOR and urea total water hydrolysis. Background Technology

[0002] Hydrogen (H2) and oxygen (O2), as clean and pollution-free energy sources, have advantages such as high energy density and no pollutants produced, and have received widespread attention, making it possible for them to replace traditional chemical energy sources as the main energy source for mankind.

[0003] There are three main traditional methods for hydrogen production: hydrogen production from water gas, hydrogen production from natural gas, and hydrogen production from water electrolysis. The first two methods still rely on traditional chemical energy sources and generate greenhouse gases such as carbon dioxide during daily production. Water decomposition yields hydrogen and oxygen, while water electrolysis does not require chemical energy; it only needs inexpensive and readily available water. Importantly, its decomposition products do not contain additional pollutants, and the production environment is relatively mild. Therefore, water electrolysis is considered one of the most promising hydrogen production methods and is worthy of further research and exploration.

[0004] Electrochemical water splitting consists of two half-reactions: the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). The electrolysis process requires overcoming the overpotential to surpass the high activation energy barrier, especially for the slow OER. However, current large-scale commercial applications still rely on expensive and scarce noble metal catalysts, including Pt, Ir, and Ru-based oxides. Unfortunately, the scarcity, high cost, and limited functionality of noble metals hinder their large-scale application. Therefore, there is an urgent need to develop a highly efficient and inexpensive water electrolysis catalyst.

[0005] It is worth noting that urea electrolysis has similar applications to water electrolysis. Urea electrolysis can not only obtain sustainable clean H2, but also purify urea-rich wastewater. Regarding urea electrolysis, since the theoretical electrode potential of UOR is 0.37V, far lower than OER (1.23V, relative to RHE), urea electrolysis can achieve a higher energy conversion efficiency compared to water electrolysis.

[0006] A synthesis method and application of a Co3S4@NiS@CNTs@NF electrode, published on October 13, 2023 (CN 116876023 A), were disclosed. The in-situ growth of Co3S4@NiS and the direct assembly of carbon nanotubes on nickel foam solved the low conductivity problem caused by the addition of binders. The carbon nanotubes also endowed the nickel foam surface with excellent specific surface area and abundant conductive channels. Furthermore, the synergistic effect of the connection between Co3S4@NiS and CNTs not only improved the electrochemical performance of Co3S4@NiS@CNTs@NF but also gave it better supercapacitor and HER electrode performance. In addition, the heterostructure of Co3S4@NiS formed multiple active sites and abundant interfaces, further improving the electrochemical performance of the multifunctional electrode. However, its application in OER, UOR, and urea water electrolysis was not disclosed.

[0007] Therefore, it is essential to develop highly efficient catalysts that can realize oxygen evolution reaction, urea oxidation reaction and total urea hydrolysis reaction under high current density. Summary of the Invention

[0008] The purpose of this invention is to prepare a multi-element sheet-like nanocomposite material and its preparation method. The multi-element sheet-like nanocomposite material is prepared by a simple two-step hydrothermal reaction using four chemical elements: rare earth element (Ce), transition non-noble metal (Co, Fe), and S. The preparation method is simple and the reaction conditions are mild.

[0009] Another objective of this invention is to provide the application of multi-component sheet-like nanocomposite materials in oxygen evolution reaction (OER), urea oxidation reaction (UOR), and total urea hydrolysis reaction (OUS). The OER process exhibits excellent catalytic performance under high current density; it also shows good performance in urea oxidation (UOR) and urea total hydrolysis catalysis; and the catalyst has excellent stability.

[0010] The specific technical solution of this invention is as follows:

[0011] A method for preparing multi-component sheet-like nanocomposites includes the following steps:

[0012] 1) Nickel foam was placed in a mixed solution of cobalt source, cerium source, organic ligand and solvent, and subjected to hydrothermal reaction to obtain nickel foam with CeO2 / Co(OH)2 precursor.

[0013] 2) The nickel foam with CeO2 / Co(OH)2 precursor prepared in step 1) is placed in a mixed solution of iron source, sulfur source and solvent, and subjected to hydrothermal reaction to obtain multi-component sheet nanocomposite material.

[0014] In step 1), the molar ratio of the cobalt source to the cerium source is 0.6–3.4:0.2–0.7;

[0015] In step 1), the molar ratio of the cobalt source, cerium source, and organic ligand is 0.6–3.4:0.2–0.7:1;

[0016] In step 1), preferably, the molar ratio of the cobalt source, cerium source, and organic ligand is 20:3:10;

[0017] In step 1), the ratio of the cobalt source to the solvent is 0.1-0.2 mol / L;

[0018] In step 1), the cobalt source is selected from soluble cobalt salts, preferably cobalt nitrate hexahydrate;

[0019] In step 1), the cerium source is selected from soluble cerium salts, preferably cerium nitrate hexahydrate;

[0020] In step 1), the organic ligand is selected from dimethylimidazole;

[0021] In step 1), the solvent is selected from a mixed solution of methanol and water, and the volume ratio of methanol to water is 2:1;

[0022] In step 1), the hydrothermal reaction refers to a hydrothermal reaction at 100–170°C for 10 hours;

[0023] In step 2), the molar ratio of the iron source to the sulfur source is 1:4;

[0024] In step 2), the ratio of the iron source to the solvent is 0.010-0.020 mol / L;

[0025] In step 2), the iron source is selected from soluble iron-sulfur, preferably ferric nitrate nonahydrate;

[0026] In step 2), the sulfur source is selected from organic sulfur sources, preferably thiourea;

[0027] In step 2), anhydrous ethanol is selected as the solvent. Using a solvent other than pure anhydrous ethanol will cause changes in the size of the material. For example, using a 2:1 mixture of ethanol and water, SEM scan results show that the size of the material increases and the electrochemical performance under the reaction conditions deteriorates.

[0028] In step 2), the hydrothermal reaction refers to a reaction at 130°C for 10 hours.

[0029] In step 2), the prepared product is a multi-component sheet-like nanocomposite material CeO2 / Co(OH)2 / FeS@NF.

[0030] In this invention, step 1) is the first hydrothermal reaction: utilizing the characteristics of hydrothermal synthesis, the reaction vessel and methanol-water solution provide the superheat and saturated vapor pressure required for crystal nucleation and growth, placing the reaction system under subcritical and supercritical conditions. At this point, substances such as cobalt nitrate hexahydrate, cerium nitrate hexahydrate, dimethylimidazole, and methanol solution exist at the molecular level. 2+ Co 2+ Uniformly binds to organic ligands and grows rapidly and uniformly on the surface of nickel foam to obtain a large number of nanosheets, providing a large number of reactive sites for subsequent reactions. After the reaction is completed, the precursor solution and a piece of cleaned nickel foam (2×3cm) are placed in the reaction vessel and reacted in the oven. After the reaction is completed, the nickel foam covered with CeO2 / Co(OH)2 precursor is carefully cleaned with water and ethanol solution and air-dried at room temperature.

[0031] Step 2) is the second hydrothermal reaction: Utilizing the excellent characteristics of hydrothermal reactions, ferric nitrate nonahydrate and thiourea are first dissolved in an ethanol solution and ultrasonically stirred for 15 minutes to form a mixed solution. Then, the mixed solution and the previously reacted nickel foam are placed in a reaction vessel to react. Because Ce... 4+ Fe 3+ The electron-deficient nature of the catalyst necessitates electron transfer between itself and elements such as S and N in thiourea, resulting in a change in catalyst size. This change provides a large number of active sites for the catalytic reaction. After the reaction, the nickel foam loaded with the multi-component nanosheet composite material was carefully washed with water and ethanol solution and allowed to air dry at room temperature.

[0032] The present invention provides a multi-component sheet-like nanocomposite material, which is prepared by the above method. The multi-component sheet-like nanocomposite material CeO2 / Co(OH)2 / FeS@NF has a morphology of a spherical flower structure composed of nanosheets, and the thickness of the nanosheets is 4-6 nm.

[0033] The multi-component sheet-like nanocomposite material provided by this invention has applications in OER, UOR, and urea complete water hydrolysis. The overpotential of the oxygen evolution reaction in 1M KOH electrolyte solution is much lower than that of RuO2 (the lower the overpotential, the better the catalytic performance); simultaneously, it exhibits extremely high catalytic performance in urea oxidation and complete water hydrolysis.

[0034] This invention utilizes a simple hydrothermal synthesis method to first synthesize electron-deficient Ce. 2+ Co 2+The combination with electron-rich organic ligands forms a homogeneous mixed solution, which makes the reaction more uniform and complete. The methanol-water solution used in the reaction process can provide the required superheat and saturated vapor pressure, which is theoretically superior to pure water solvent. Given the aforementioned reaction conditions, the reaction proceeds rapidly and grows uniformly on the surface of nickel foam. XRD results show that an electron-deficient Ce-containing alloy was prepared. 4+ and Co 2+ The compound, as determined by scanning, exhibits a nanosheet-like morphology. This sheet-like structure provides numerous reactive sites for subsequent reactions. Building upon the previous preparation, selective design was employed, choosing elements that readily donate electrons, such as S and N, to enable them to react with Ce. 4+ and Co 2+ Fe 3+ The second step involves electron transport, followed by hydrothermal treatment based on Fe. 3+ Due to the electron deficiency of Fe and the electron-rich nature of elements such as S and N in thiourea, ferric nitrate nonahydrate and thiourea are added. 3+ Due to the easy hydrolysis of the material, ethanol was used as a solvent during the reaction. Characterization after the reaction revealed that a CeO2 / Co(OH)2 / FeS@NF composite material was prepared by XRD, and scanning spectroscopy showed that its morphology consisted of smaller nanosheets. Compared to comparative examples 1-3 of this invention, this morphology provides a large number of reactive sites for the reaction, which was confirmed by electrochemical LSV testing.

[0035] Compared with existing technologies, this invention has the following advantages: the preparation method is simple, the reaction conditions are mild, and the required reagents and equipment are simple; the use of non-precious metals and rare earth elements as raw materials greatly reduces costs; it exhibits excellent catalytic performance under high current density during the OER process; it shows good performance in urea oxidation (UOR) and urea total water splitting catalysis; and the catalyst has excellent stability. The synthesized electrochemical catalyst can be used for oxygen evolution reaction (OER), urea oxidation reaction (UOR), and total urea hydrolysis reaction (OUS). Attached Figure Description

[0036] Figure 1 This is a scanning electron microscope image of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0037] Figure 2 This is a transmission electron microscope (TEM) image of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0038] Figure 3 The image shows the X-ray diffraction (XRD) pattern of the multi-component sheet-like nanocomposite material prepared in Example 1.

[0039] Figure 4The X-ray energy dispersive X-ray spectrum (EDX) of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0040] Figure 5 X-ray energy dispersive spectroscopy (EDS) data of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0041] Figure 6 This is a mapping diagram of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0042] Figure 7 Scanning electron microscope image of the precursor prepared in Comparative Example 1;

[0043] Figure 8 Transmission electron microscope image of the precursor prepared in Comparative Example 1;

[0044] Figure 9 Scanning electron microscope (SEM) image of the material prepared in Comparative Example 2;

[0045] Figure 10 Scanning electron microscope (SEM) image of the material prepared in Comparative Example 3;

[0046] Figure 11 Polarization curves of nanomaterials prepared in Example 1 and Comparative Examples 1, 2, and 3, and commercial RuO2 in 1M KOH solution;

[0047] Figure 12 Polarization curves of nanomaterials prepared in Example 1 and Comparative Examples 1, 2, and 3, and commercial RuO2 in 1M KOH (+0.33M Urea) solution;

[0048] Figure 13 The polarization curves of the products of Example 1 and Comparative Example 1 in the catalytic reaction of total water hydrolysis in 1M KOH solution and the polarization curves of the catalytic reaction of total urea hydrolysis in 1M KOH + 0.33M Urea solution are shown.

[0049] Figure 14 To demonstrate the stability of Example 1 in 1M KOH solution;

[0050] Figure 15 The stability of Example 1 in a 1M KOH (+0.33M Urea) solution;

[0051] Figure 16 XPS of the multi-component sheet-like nanocomposite material prepared in Example 1;

[0052] Figure 17 Scanning electron microscope image of the material prepared in Comparative Example 4;

[0053] Figure 18 Scanning electron microscope image of the material prepared in Comparative Example 5. Detailed Implementation

[0054] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.

[0055] The raw materials collected for the synthesis of this invention are: cobalt nitrate hexahydrate, cerium nitrate hexahydrate, dimethylimidazole, methanol, urea, ferric nitrate nonahydrate, thiourea, deionized water, and nickel foam (2×3cm).

[0056] The materials characterization instruments used in this invention include: transmission electron microscope (HT7700), field emission scanning electron microscope (Hitachi 8100), X-ray powder diffractometer (Smart Lab), EDS, etc.

[0057] Electrochemical testing of this invention: CHI760E.

[0058] Example 1

[0059] The preparation of a multi-component sheet-like nanocomposite material CeO2 / Co(OH)2 / FeS@NF includes the following steps:

[0060] 1) First step hydrothermal reaction: Cerium nitrate hexahydrate (0.145g), cobalt nitrate hexahydrate (0.58g), dimethylimidazole (0.082g), and 15mL of methanol-water solution (volume ratio V methanol:V deionized water = 2:1) were ultrasonically mixed and stirred until the solution turned purple-red. The above mixed solution and a piece of cleaned nickel foam (2×3cm) were placed in the reaction vessel and hydrothermally reacted in an oven at 150℃ for 10h. After the reaction vessel cooled to room temperature, the nickel foam covered with CeO2 / Co(OH)2 was removed, carefully cleaned with water and ethanol solution, and allowed to air dry.

[0061] 2) Second step hydrothermal reaction: Dissolve ferric nitrate nonahydrate (0.1g) and thiourea (0.076g) in 15ml of anhydrous ethanol and stir for 15min. Place the solution and the above-prepared nickel foam in a reaction vessel and react at 130℃ for 10h. After the reaction is completed, the nickel foam of CeO2 / Co(OH)2 / FeS multi-element sheet nanocomposite material is carefully cleaned with water and ethanol solution and air-dried naturally.

[0062] The multi-component sheet-like nanocomposite material CeO2 / Co(OH)2 / FeS nickel foam prepared according to the above preparation method was analyzed by scanning electron microscopy and transmission electron microscopy. Figure 1 , Figure 2 Its morphology was observed, confirming it as a nanoflora structure. X-ray diffraction was then performed. Figure 3 The material was determined to be composed of CeO2, Co(OH)2, and FeS multi-component substances, as confirmed by EDX testing. Figure 4 , Figure 5The tests further confirmed its elemental composition, and also proved that the material is composed of Ce, Co, Fe, and S. Figure 6 Mapping further confirmed the presence of Ce, Co, Fe, and S. XPS testing showed that Ce, Co, Fe, and S all exist in ionic states. XRD results indicated the absence of other Ni compounds, with only elemental nickel peaks present. The prepared catalyst is composed of three phases: CeO2, Co(OH)2, and FeS. EDS and mapping results confirmed the presence of Ce, Co, Fe, and S elements. SEM and TEM results showed that the material has a morphology of nanosheets with a size of approximately 5 nm. XPS testing was performed on the prepared catalyst to characterize its chemical state and electronic structure. Characteristic peaks of Ce, Co, Fe, and S were observed in the full XPS spectrum, indicating its elemental composition. XPS peak fitting was used to separate Ce. 4+ Fe 2+ S 2- Co 2+ This demonstrates the material composition of the catalyst, which is another proof of the previous material characterization.

[0063] Comparative Example 1

[0064] According to Example 1, only the first step of the hydrothermal reaction was performed to obtain nickel foam with fully grown CeO2 / Co(OH)2@NF, labeled as: CeCo@NF; Figure 7 , Figure 8 The results show that the prepared CeCo@NF catalyst is composed of Co(OH)2 and CeO2, and its size is about 10 nm. The difference from Example 1 is the number and size of the sheets.

[0065] Comparative Example 2

[0066] The process was carried out according to Example 1, except that the second step of the hydrothermal reaction was controlled by adding only ferric nitrate nonahydrate to the solution to obtain CeO2 / Co(OH)2 / Fe@NF, labeled as: CeCoFe@NF; Figure 9 The results indicate that the product is composed of CeO2 and Co(OH)2. Due to the absence of S, the Fe element in the material exists in the form of other hydrates, resulting in uneven growth of nanosheets and a very small number of nanosheets with a size of about 20 nm.

[0067] Comparative Example 3

[0068] The process was carried out according to Example 1, except that the second step of the hydrothermal reaction was controlled by adding only thiourea to the solution to obtain CeO2 / Co(OH)2 / S@NF, labeled as CeCoS@NF; Figure 10The product is composed of CeO2 and Co(OH)2. Due to the absence of Fe, the S element in the material cannot combine with Fe, resulting in a huge difference in its morphology. It changes from a sheet-like shape to other morphologies, and its size becomes a blocky structure of 500 nanometers.

[0069] Comparative Example 4

[0070] The procedure was carried out according to Example 1, except that the hydrothermal reaction temperature in the second step was changed from 130°C to 150°C. The morphology of the product is as follows. Figure 17 .

[0071] Comparative Example 5

[0072] The procedure was carried out as in Example 1, except that anhydrous ethanol was replaced with an ethanol solution, and the volume ratio of ethanol to water was 2:1. The morphology of the product is as follows. Figure 18 SEM scan results show that as the material size increases, its electrochemical performance deteriorates under these reaction conditions.

[0073] After testing, it was found that the performance and characterization of the material obtained by adding Fe and S at the same time were better than those obtained by adding them alone. In contrast, the second step of Example 4, due to the increase in temperature, changed the crystal growth rate, which led to the difference in the morphology of the material. In summary, Fe, S and temperature have a certain influence on the morphology of the material.

[0074] Application Example 1:

[0075] The application of the multi-component sheet-like nanocomposite CeO2 / Co(OH)2 / FeS@NF catalyst includes the following steps:

[0076] Methods: The nickel foams prepared in 1×1 cm samples from Examples 1, 1, 2, and 3 were used for performance testing. 3 mg RuO2, 2 mg carbon black, and 1 mg PVDF were weighed, mixed, and ground evenly. Then, 50 mL of N-methylpyrrolidone was added, and the mixture was stirred further before being coated onto the cleaned nickel foam. A three-electrode system was used in the test, employing a CHI760 workstation. A platinum sheet was used as the counter electrode, the nickel foam electrode as the working electrode, and a silver chloride electrode as the reference electrode. The electrolyte was a 1 M potassium hydroxide solution. The OER curve was obtained through cyclic polarization (LSV) curves. Figure 11 The stability of the CeO2 / Co(OH)2 / FeS@NF catalyst, a multi-layer sheet-like nanocomposite material, was measured by constant voltage. In the oxygen evolution reaction (OER), the stability was assessed at current densities of 20 and 200 mA cm⁻¹. -2At the same time, the overpotentials of the CeO2 / Co(OH)2 / FeS@NF catalyst prepared in Example 1 were 187 and 224 mV, respectively, while the overpotentials of the CeO2 / Co(OH)2@NF catalyst prepared in Comparative Example 1 (without Fe and S) were 187 and 224 mV, respectively, at a current density of 20 mA cm⁻¹. -2 The overpotential at the specified time was 332 mV, which is far lower than that of Example 1. Comparative Example 2 (without S) CeO2 / Co(OH)2 / Fe@NF catalyst at a current density of 20 mA cm⁻¹ -2 The overpotential at that time was 254 mV. Comparative Example 3 (Fe-free) CeO2 / Co(OH)2 / S@NF catalyst could not be read beyond 20 mA cm⁻¹ due to the presence of the oxidation peak. -2 The overpotential is below 200 mA cm⁻¹, but the material is at 200 mA cm⁻ -2 The current density is 314 mV, which is far lower than that of CeO2 / Co(OH)2 / FeS@NF. In summary, by comparing the presence and absence of Fe and S, it can be seen that only the addition of Fe and S elements achieves optimal performance. Compared with the traditional RuO2 catalyst, RuO2 exhibits better performance at a current density of 20 mA / cm². -2 The overpotential at that time was 266mV, which is far lower than that of the prepared catalyst.

[0077] Application Example 2

[0078] The application of the multi-component sheet-like nanocomposite CeO2 / Co(OH)2 / FeS@NF catalyst in the urea oxygen evolution reaction includes the following steps:

[0079] Method: The test method was the same as in Application Example 1, except that 0.33M urea was added to the 1M KOH electrolyte. In the urea oxidation reaction (UOR), the current density was 10 mA cm⁻¹. -2 At that time, the potential of the CeO2 / Co(OH)2 / FeS@NF catalyst prepared in Example 1 was 1.30 V, while the potential of the CeO2 / Co(OH)2@NF catalyst prepared in Comparative Example 1 (without Fe and S) could not be read at 10 mA cm⁻¹ due to the presence of oxidation peaks. -2 The overpotential at current density, as shown by the LSV curve, is lower than that of the prepared catalyst, while the overpotential of the conventional RuO2 catalyst at 10 mA cm⁻¹ is lower. -2 The overpotential at the current density was 1.34V. The overall UOR polarization curve of the CeO2 / Co(OH)2 / FeS@NF catalyst, a multi-layered sheet-like nanocomposite, shows that a lower overpotential and better catalytic performance are observed at higher current densities. According to... Figure 12 The LSV curves show that, in Comparative Examples 2 and 3, at a current density of 10 mA cm⁻¹ -2The true values ​​of the oxidation peaks could not be read due to their presence, but overall it can be seen that the performance of Examples 2 and 3 is worse than that of the CeO2 / Co(OH)2 / FeS@NF catalyst.

[0080] Application Example 3

[0081] The application of the multi-component sheet-like nanocomposite CeO2 / Co(OH)2 / FeS@NF catalyst in the complete hydrolysis of urea includes the following steps:

[0082] Method: Two 1cm × 1cm nickel foam pieces of catalyst from Example 1 and Comparative Example 1 were used as the cathode and anode, respectively. The electrolytes were 1M KOH and 1M KOH + 0.33M Urea solution. Testing was conducted using a CHI760 workstation, and the total water hydrolysis performance curves and urea hydrolysis performance curves were obtained through polarization curves (LSV). Figure 13 As shown. At a current density of 10 mA cm⁻¹ -2 At that time, the potential of the catalyst prepared in Example 1 was 1.43V.

[0083] Comparative Examples 2 and 3 were not tested because the selection of the anode and cathode for the complete hydrolysis of urea was based on the previous performance study of the catalyst OERUOR. Comparative Examples 2 and 3 showed poor performance in the previous tests, so they were not considered further. Traditional RuO2, such as... Figure 13 As shown in curve 5. A two-electrode electrolytic cell was established in 1M KOH and 1M KOH + 0.33M Urea solutions using CeO2 / Co(OH)2 / FeS@NF as the cathode and anode for testing.

[0084] Figure 14 , 15 The tests were conducted using a standard three-electrode system in alkaline 1M KOH and 1M KOH + 0.33M urea solutions, respectively. A predetermined current density was maintained during the tests, and the system was allowed to run for a specified period. The results showed that the catalyst exhibited good performance under a constant current density of 200 mA / cm². -2 The OER performance remained stable for 25 hours, with minimal change in potential amplitude before and after. Figure 15 The results showed that this catalysis was effective at 10 mA cm⁻¹. -2下 The UOR performance can maintain stability for 30 hours.

[0085] The above-described detailed description of the preparation of the multi-component sheet-like nanocomposite CeO2 / Co(OH)2 / FeS@NF and the study of its OER, UOR and urea hydrolysis performance under alkaline high current conditions is illustrative rather than limiting. Several examples can be listed within the defined scope. Therefore, variations and modifications that do not depart from the overall concept of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing multi-component sheet-like nanocomposite materials, characterized in that, The preparation method includes the following steps: 1) Nickel foam was placed in a mixed solution of cobalt source, cerium source, organic ligand and solvent, and subjected to hydrothermal reaction to obtain nickel foam with CeO2 / Co(OH)2 precursor. 2) The nickel foam with CeO2 / Co(OH)2 precursor prepared in step 1) was placed in a mixed solution of iron source, sulfur source and solvent, and hydrothermally reacted to obtain a multi-component sheet-like nanocomposite material. In step 1), the solvent is selected from a mixed solution of methanol and water, wherein the volume ratio of methanol to water is 2:1; the organic ligand is selected from dimethylimidazole. In step 2), the sulfur source is selected from thiourea, the hydrothermal reaction refers to the reaction at 130°C for 10 hours, and the solvent is anhydrous ethanol.

2. The preparation method according to claim 1, characterized in that, In step 1), the molar ratio of the cobalt source, cerium source and organic ligand is 0.6~3.4:0.2~0.7:

1.

3. The preparation method according to claim 1 or 2, characterized in that, In step 1), the hydrothermal reaction refers to a hydrothermal reaction at 100~170℃ for 10 hours.

4. The preparation method according to claim 1, characterized in that, In step 2), the molar ratio of the iron source to the sulfur source is 1:

4.

5. A multi-component sheet-like nanocomposite material prepared by the preparation method according to any one of claims 1-4.

6. The application of a multi-component sheet-like nanocomposite material prepared by the preparation method according to any one of claims 1-4 in OER, UOR and urea total hydrolysis.

Citation Information

Patent Citations

  • Synthesis method and application of Co3S4 (at) NiS (at) CNTs (at) NF electrode

    CN116876023A